2020
DOI: 10.1111/inm.12826
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID‐19 on nurses working in a University Health System in Singapore: A qualitative descriptive study

Abstract: Given Singapore’s high population density and extensive geographical interconnections, it is unsurprising that the country reported one of the highest numbers of COVID‐19 cases in Asia. Past pandemic studies have suggested that nurses working in such crises might experience a deterioration of mental health, which could persist for years beyond the initial outbreak. This study used a qualitative descriptive design to explore nurses’ experiences of working in tertiary hospitals during the COVID‐19 pandemic. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(135 citation statements)
references
References 35 publications
11
116
3
5
Order By: Relevance
“…These results are in accordance with cases of medical healthcare workers that demonstrated positive associations between the severity of perceived threat for COVID-19 or being at risk of contact with COVID-19 patients versus reports of depressive symptoms, anxiety, and insomnia [44,58,59]. Fear of contracting COVID-19 at work is associated with higher emotional exhaustion and depersonalization [45] and could be one of the most prominent distress for medical professionals with frequent contacts with COVID-positive patients [54,57,60]. Second, perceived stigma from family and friends (worries for possible transmission of infection through PHDs at frontline) and rejection from neighborhood [ex.…”
Section: Perceived Threat Of Infection Stigma and Social Rejection And Mental Healthsupporting
confidence: 86%
“…These results are in accordance with cases of medical healthcare workers that demonstrated positive associations between the severity of perceived threat for COVID-19 or being at risk of contact with COVID-19 patients versus reports of depressive symptoms, anxiety, and insomnia [44,58,59]. Fear of contracting COVID-19 at work is associated with higher emotional exhaustion and depersonalization [45] and could be one of the most prominent distress for medical professionals with frequent contacts with COVID-positive patients [54,57,60]. Second, perceived stigma from family and friends (worries for possible transmission of infection through PHDs at frontline) and rejection from neighborhood [ex.…”
Section: Perceived Threat Of Infection Stigma and Social Rejection And Mental Healthsupporting
confidence: 86%
“…A recent qualitative research study verified that support from family, friends, colleagues, organizations, and the public is crucial to promote nurses' well-being during the COVID-19 pandemic. The same study suggests that institutions implement communication strategies between managers and nurses to promote the use of strategies to reduce stress and provide accurate information; provide support in basic daily needs; and promote psychosocial support, such as groups to express emotions [41]. Another recent study suggests psychoeducational interventions for nurses to promote coping strategies and reduce psychological symptomatology [15].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, promoting resilience is crucial for nurses coping with work-related stress [44]. Furthermore, a strong support system is essential to promote resilience in nurses [41].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of quarantine is to reduce the risk of infection, not to limit interpersonal contact, which will affect the mental health of doctors and nurses (19). Goh et al also found that nurses reported physical and psychological challenges relating to working conditions of the hospital in the initial months of the pandemic in Singapore (20).…”
Section: Discussionmentioning
confidence: 99%